HR-Benchmarking as an Innovative Tool of Personnel Management in Ukraine - Kazak, Ðžlena; Shevchenko, Ðžlena; ., . (International Journal of Engineering and Technology, 2018)
The essence of benchmarking and its kind as HR-benchmarking is revealed.Â First of all, the emphasis is on HR-benchmarkingÂ as the process of identifying and adapting existing examples of HR services effective functioning to improve their performance in a particular company, and also methods and motivational tools for effective impact on staff.Â The basic approaches to the classification of HR-metrics, which analyze HR-services, are determined.Â The reasons that hinder the effective implementation of HR-benchmarking in enterprises of Ukraine are being analyzed, which is connected, first of all, to the peculiarities of doing business, differences in thinking, motivation, views on human resources, in relation to the work of the employees themselves.Â The expediency of using HR-benchmarking in the implementation of innovative digital technologies at domestic enterprises it is discussed, which form the digital management of career development, work rotation and continuous training of employees, improving the HR services.Â Â Â